Komposisi Dan Distribusi Plankton Prakemunculan Nike Di Perairan Teluk Gorontalo Provinsi Gorontalo - Abdul Hafidz Olii; Thomas Tammu; Femy M Sahami (JURNAL GALUNG TROPIKA, 2022)
The purpose of this study was to determine the composition of the abundance of Nike pre-emergence plankton in the waters of Gorontalo Bay, Gorontalo Province. Sampling was carried out in the Nike catching area at the time of Nike's pre-emergence using a plankton net mesh size of 25 m which was drawn horizontally on the water surface layer with a depth of (30-100 cm) fourth reasons of the Nike pre-emergence period, namely from July to September 2021. The results showed that spatially temporally plankton had a high abundance at the location where Nike fish appeared and the abundance of plankton affected the appearance of Nike fish on the first day in the water-soft Gorontalo Bay, while Nike had eating habits from the Bacillariophyceae group which was the group with the highest abundance spatially and temporally during the study.